2022
DOI: 10.1108/jcms-11-2021-0037
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of international market indices for measuring market efficiency based on price-volume relationship

Abstract: PurposeThe main purpose of the research is to determine if the relationship between trading volume and price changes is connected to market effectiveness and to use the volume-price relationship to compare the efficiency levels of foreign markets. The degree of the relationship is determined in this study, and the efficiency levels of different countries' capital markets are compared.Design/methodology/approachIn this study, 1,024 observations are used as a data set, which includes daily closing prices and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…They concluded that speculative activity is responsible for increased volatility in the futures price as the contract approaches maturity. Sunay (2022) found strong price volume relationship in the US market. But no such relationship was observed in other markets.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They concluded that speculative activity is responsible for increased volatility in the futures price as the contract approaches maturity. Sunay (2022) found strong price volume relationship in the US market. But no such relationship was observed in other markets.…”
Section: Review Of Literaturementioning
confidence: 99%